An Efficient Adaptive Anticollision Algorithm Based on 4-Ary Pruning Query Tree. (21st December 2013) - Zhang, Wei; Guo, Yajun; Tang, Xueming; Cui, Guohua; Wu, Longkai; Mei, Ying
In radio frequency identification system (RFID), the efficiency in which the reader identifies multiple tags is closely related to the methods to solve the collision of multiple tags. At present, a reasonable solution is the introduction of 4-ary query tree (or n -ary query tree) to reduce the collision time slots and additional query is used to decrease idle timeslots. The advantage of a 4-ary tree anti-collision algorithm is that it is able to reduce collision timeslots, but it also increases the idle timeslots. To reduce these excessive idle timeslots the 4-ary tree anticollision algorithm brings, an anti-collision algorithm based on adaptive 4-ary pruning query tree (A4PQT) is proposed in this paper. On the basis of the information of collision bits, some idle timeslots can be eliminated through pruning the 4-ary tree. Both theoretical analysis and simulation results support that A4PQT algorithm can significantly reduce recognition time and improve throughput of the RFID system.